The Effectiveness of Short Story To Improve Students’ Reading Comprehension - Donny Adiatmana Ginting; Muhammad Hasan; Muhammad Syafi'i (LPPM STKIP AL MAKSUM, 2020)
This research aims to know the effectiveness of the Short Story to improve students’ reading comprehension. The design of the study is experimental research that consists of two classes; experiment and control classes. The research includes pre-test and post-test. The population is 60 and the sample is 40 students. The researcher uses simple random sampling to determine the sample of the study. In the pre-test data, the mean score of the experiment class is 60,69, and the mean score of the control class is 64,1. In post-test data, the mean score of the experimental class is 86.90, and the mean score of the control class is 62,25. Based on the analysis of the pre-test data, the value of Tcounted is 0,015, which is compared with Ttable is 1.685 or Tcounted < Ttable. It can be stated that there is no effect on pre-test data. Based on the analysis of the post-test data, the value of Tcounted is 1,801 that compared with Ttabel is 1.685 or Tcounted > Ttable , Ha is accepted. The Stort Story was effective to improve the students’ reading comprehension